Typification of Terfezia fanfani (Ascomycota, Pezizaceae) - Vizzini, Alfredo; Arenas, Francisco; Rodríguez, Antonio; Mello, Antonietta; Lainé, Patrice; Muñoz-Mohedano, Justo M.; Morte, Asunción (Phytotaxa, 2019)
Terfezia fanfani Mattirolo (1900: 65) is an ecologically distinctive species that is widely distributed in southern Europe in areas with Mediterranean climates, on acidic grasslands, associated with Tuberaria guttata (Cistaceae) from March to May (Bordallo et al. 2013).